Can integrating religiosity and spirituality into postpartum care improve the quality of life in women with preeclampsia - Rasouli, Robab; Maleki, Azam; Zenoozian, Saeedeh (Frontiers in Psychiatry, 2023)
Background: Women with a history of preeclampsia frequently have a lower level of physical well-being and emotional problems. Objective: This study aimed to determine the effect of integrating religiosity and spirituality into postpartum care can improve the quality of life in women with preeclampsia. Methods: This study was a randomized controlled clinical trial conducted on 40 women with preeclampsia. All eligible participants were allocated to two control and intervention groups using a random blocking method. Data were collected using Mother-Generated Index (MGI) in pre-intervention and six weeks later and analyzed using descriptive statistics, Chi-square test, and independent t-tests. The significance level was p <0.05. Results The mean, Standard deviation (SD) of the total score of MGI before intervention in the intervention group was 5.35(1.09) which increased to 8.00(0.50) six weeks after intervention. In the control group, the pre-test score of MGI was 5.81(0.97) which increased to 6.69(1.37) after six weeks of follow-up. The difference between the two groups was statistically significant after the intervention based on an independent t-test (p=0.001). The mean (SD) of five subscales included Feelings towards herself, Feelings toward the child, Feelings toward her husband and others, Feelings toward sex, and Physical health status after intervention in the intervention group statistically significantly increased compared to the control group(p<0.011). Conclusion The integration of spiritual counseling with the educational content of postpartum care had a positive impact on improving the postpartum QoL of women with preeclampsia. It can be used for planning suitable interventions among postnatal women.